1999
DOI: 10.1042/bj3400143
|View full text |Cite
|
Sign up to set email alerts
|

When and why a water-soluble antioxidant becomes pro-oxidant during copper-induced low-density lipoprotein oxidation: a study using uric acid

Abstract: The inclusion of uric acid in the incubation medium during copper-induced low-density lipoprotein (LDL) oxidation exerted either an antioxidant or pro-oxidant effect. The pro-oxidant effect, as mirrored by an enhanced formation of conjugated dienes, lipid peroxides, thiobarbituric acid-reactive substances and increase in negative charge, occurred when uric acid was added late during the inhibitory or lag phase and during the subsequent extensive propagation phase of copper-stimulated LDL oxidation. The pro-oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
1
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(89 citation statements)
references
References 43 publications
2
83
1
3
Order By: Relevance
“…21 Despite this, several studies have demonstrated that uric acid can be prooxidative and may generate free radicals. [22][23][24][25] The ability to activate p38 MAPK, NF-kB, and AP-1, as well as to increase MCP-1 expression, is consistent with an oxidantdriven pathway. 26,27 In conclusion, we have found that uric acid can induce inflammatory pathways in rat VSMCs in vitro, with activation of p38 MAPK, NF-B, and AP-1 and increased expression of COX-2 and MCP-1.…”
Section: Discussionmentioning
confidence: 67%
“…21 Despite this, several studies have demonstrated that uric acid can be prooxidative and may generate free radicals. [22][23][24][25] The ability to activate p38 MAPK, NF-kB, and AP-1, as well as to increase MCP-1 expression, is consistent with an oxidantdriven pathway. 26,27 In conclusion, we have found that uric acid can induce inflammatory pathways in rat VSMCs in vitro, with activation of p38 MAPK, NF-B, and AP-1 and increased expression of COX-2 and MCP-1.…”
Section: Discussionmentioning
confidence: 67%
“…Clinical studies have revealed higher or unchanged protein carbonyls in patients with high urate, including refractory gout patients (30)(31)(32). Furthermore, urate has the capacity to act as a prooxidant under some circumstances (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have revealed similar properties in other common antioxidants, including flavonoids [30], nonflavonoid phenols [36], cysteine [37,38], and urate [39][40][41]. The effects of ascorbate are further complicated by the fact that dehydroascorbate, the product of its two-electron oxidation, can itself act as both a pro-oxidant and an antioxidant toward LDL [24,26,35,42].…”
Section: Introductionmentioning
confidence: 99%